An improved solar PV system for Malaysian rural electrification - Part I: Design and testing of solar PV with tracker and reflectors - Malek N.Abd.; Hasini H.; Rahman A.Abd.; Jaafar Mohd.N.Mohd. (2023)
This paper is the first of a set describing the investigation on an improved solar photovoltaic (PV) system for specific application in Malaysian rural electrification. The application will be applied as part of the renewable energy solutions for the underserved communities with particular emphasis given to local and native villages in Sabah and Sarawak. The paper presents recommended design and testing of a stand-alone PV system carried out to confirm its effectiveness as compared to the conventional solar PV system. In order to achieve a reliable long-term performance of the PV system, reflectors and solar tracker are adopted into the system and its performance characteristics are carefully investigated via experiment. The efficiency and performance of the new solar PV system were calculated and compared with the conventional one. It has been demonstrated that the solar PV system with solar tracker and reflectors showed good performance improvement as compared to the conventional module. 2010 IEEE.